Perbedaan Pandangan Hakim Dalam Penetapan Tersangka Sebelum dan Sesudah Putusan Mahkamah Konstitusi Nomor 21/PUU-XII/2014 - Afrizal Chair Nawar; Syafruddin Kalo; Madiasa Ablisar; Mahmud Mulyadi (USU LAW JOURNAL, 2019)
Abstract. In practice, the use of pretrial mechanisms is often not optimal, which can be seen from the lack of use of this mechanism in criminal proceedings. In fact, pretrial is the right of all suspects/defendants when their civil liberties are confiscated, besides that there are differences in the Supreme Court's attitude towards the determination of suspects through pretrial processes in a number of decisions, making the new legal problem now, therefore a legal study is needed to discuss differences attitude towards these pretrial decisions. The problems raised in this study, namely how is the legal regulation of the determination of suspects through pretrial decisions according to criminal procedural law, legal arguments for differences in attitudes of the Supreme Court regarding the determination of suspects before and after the Constitutional Court Decision Number 21/PUU-XII/2014, and differences the views of judges in pretrial regarding the determination of suspects after the birth of the Constitutional Court Decision Number 21/PUU-XII/2014. To find answers to these problems, this study uses a type of normative legal research that is descriptive analytical, where normative legal research uses secondary data as the main data by using data collection techniques carried out by means of library research (library reseacrh), and data analysis using methods qualitative data analysis.   Keywords: pretrial, determination of suspects, judges.